Peroxiredoxins and Hypoxia-Inducible Factor-1α in Duodenal Tissue: Emerging Factors in the Pathophysiology of Pediatric Celiac Disease Patients - Köse, Fadime Aydın; Pabuccuoglu, Aysun; Karakoyun, Miray; Aydogdu, Sema (Current Issues in Molecular Biology, 2023)
Celiac disease (CD) is an autoimmune enteropathy. Peroxiredoxins (PRDXs) are powerful antioxidant enzymes having an important role in significant cellular pathways including cell survival, apoptosis, and inflammation. This study aimed at investigating the expression levels of all PRDX isoforms (1–6) and their possible relationships with a transcription factor, HIF-1α, in the small intestinal tissue samples of pediatric CD patients. The study groups consisted of first-diagnosed CD patients (n = 7) and non-CD patients with functional gastrointestinal tract disorders as the controls (n = 7). The PRDXs and HIF-1α expression levels were determined by using real-time PCR and Western blotting in duodenal biopsy samples. It was observed that the mRNA and protein expression levels of PRDX 5 were significantly higher in the CD patients, whereas the PRDX 1, -2, and -4 expressions were decreased in each case compared to the control group. No significant differences were detected in the PRDX 3 and PRDX 6 expressions. The expression of HIF-1α was also significantly elevated in CD patients. These findings indicate, for the first time, that PRDXs, particularly PRDX 5, may play a significant role in the pathogenesis of CD. Furthermore, our results suggest that HIF-1α may upregulate PRDX-5 transcription in the duodenal tissue of CD.